2008
DOI: 10.1039/b713648j
|View full text |Cite
|
Sign up to set email alerts
|

Tetraalkylammonium amino acids as functionalized ionic liquids of low viscosity

Abstract: Four of nine tetraalkylammonium-based amino-acid ionic liquids prepared in this work show lower viscosities than all amino acid-based ionic liquids found in the literature and their reversible CO(2) absorption approaches 0.5 mol per mol ionic liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(152 citation statements)
references
References 15 publications
1
141
1
Order By: Relevance
“…[12][13][14] Inspiringly, Bates et al showed that amino-functionalised ILs were another good choice for CO 2 absorption and proAbstract: A series of 20 dual aminofunctionalised phosphonium ionic liquids, (3-aminopropyl) Keywords: amino acids · carbon dioxide capture · ionic liquids · phosphorus · physicochemical properties posed an absorption mechanism. [15] There are mainly two types of amino-functionalised ILs for CO 2 absorption: ILs in which the cations are functionalised with an appended amine group, for example, 1-(3-aminopropyl)-3-butylimid- [15] which is not as stable as phosphonium IL, [16] and ILs in which the anions are functionalised with an appended amine group, [16][17][18][19] for example, the tetrabutylphosphonium aminoethanoic acid salt ([P 4444 ]A C H T U N G T R E N N U N G [Gly]). These two types of functional ILs can absorb CO 2 in a ratio of 0.5 mol CO 2 per mol IL at room temperature and normal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Inspiringly, Bates et al showed that amino-functionalised ILs were another good choice for CO 2 absorption and proAbstract: A series of 20 dual aminofunctionalised phosphonium ionic liquids, (3-aminopropyl) Keywords: amino acids · carbon dioxide capture · ionic liquids · phosphorus · physicochemical properties posed an absorption mechanism. [15] There are mainly two types of amino-functionalised ILs for CO 2 absorption: ILs in which the cations are functionalised with an appended amine group, for example, 1-(3-aminopropyl)-3-butylimid- [15] which is not as stable as phosphonium IL, [16] and ILs in which the anions are functionalised with an appended amine group, [16][17][18][19] for example, the tetrabutylphosphonium aminoethanoic acid salt ([P 4444 ]A C H T U N G T R E N N U N G [Gly]). These two types of functional ILs can absorb CO 2 in a ratio of 0.5 mol CO 2 per mol IL at room temperature and normal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In the alanine-IL systems, the highest A.A. (mol/mol) was obtained in the absence of water, which is contrastive to the other two systems which showed significant CO 2 absorption in the presence of large amounts of water. As for the alanine system, some literature data are available in addition to that by Anderson et al [10]; according to Jiang et al [3], the mol-base A. to evaluate the recyclability of the DM. Figure 3 and Table 3 show only a typical In order to figure out what caused the higher performance, we first examine the A.A. values of the respective bulk systems.…”
Section: Co2 Absorption Measurementsmentioning
confidence: 99%
“…There are mainly two types of aminofunctionalized ILs for CO 2 absorption: ILs in which the cations are functionalized with an appended amine group, e.g., 1-(3-aminopropyl)-3-butylimid-azolium tetrafluoroborate ([aPbim][BF 4 ]) [35], which is not as stable as asphosphonium IL [16] and ILs in which the anions are functionalized with an appended amine group [75,[91][92][93], e.g., the tetrabutylphosphoniumaminoethanoic acid salt ([P 4444 ][Gly]). These two types of functional ILs can absorb CO 2 in a ratio of 0.5 mol CO 2 per mol IL at room temperature and normal pressure.…”
Section: Effect Of Ils In Gas Separation Performance Of Silmsmentioning
confidence: 99%